DEVELOPMENT OF DISEASES OF STUDENTS - O.M. Chernenko; O.O. Lysenko (Academy of Cognitive and Natural Sciences, 2009)
The problem of improvement of health in the training of future rescuers for professional activity is viewed, which is connected with the complex of factors of the worsening of young people's health.